Interaction With 14-3-3 Correlates With Inactivation of the RIG-I Signalosome by Herpesvirus Ubiquitin Deconjugases - Gupta, Soham; Ylä-Anttila, Päivi; Sandalova, Tatyana; Achour, Adnane; Masucci, Maria G. (Frontiers in Immunology, 2020)
The hijacking of cellular function through expression of proteins that interfere with the activity of cellular enzymes and regulatory complexes is a common strategy used by viruses to remodel the cell environment in favor of their own replication and spread. Here we report that the ubiquitin deconjugases encoded in the N-terminal domain of the large tegument proteins of Epstein-Barr virus (EBV), Kaposi Sarcoma herpesvirus (KSHV) and human cytomegalovirus (HCMV), but not herpes simplex virus-1 (HSV-1), target an early step of the IFN signaling cascade that involves the formation of a trimolecular complex with the ubiquitin ligase TRIM25 and the 14-3-3 molecular scaffold. Different from other homologs, the HSV-1 encoded enzyme fails to interact with 14-3-3, which correlates with failure to promote the autoubiquitination and sequestration of TRIM25 in cytoplasmic aggregates, and inability to block the activation and nuclear translocation of the IRF3 transcription factor. These findings highlight a key role for 14-3-3 molecular scaffolds in the regulation of innate immune response to herpesvirus infections and points to a possible target for the development of a new type of antivirals with applications in a broad spectrum of human diseases.